The facilitative influence of phonological similarity and neighborhood frequency in speech production in younger and older adults - VITEVITCH, MICHAEL S. (2003)
A tip-of-the-tongue (TOT) elicitation task and a picture-naming task were used to examine the role of neighborhood frequency as well as word frequency and neighborhood density in speech production. As predicted for the younger adults in Experiment 1, more TOT states were elicited for words with low word frequency and with sparse neighborhoods. Contrary to predictions, neighborhood frequency did not significantly influence retrieval of the target word. For the older adults in Experiment 2, however, more TOT states were elicited for words with low neighborhood frequency. Furthermore, in Experiment 3, pictures with high neighborhood frequency were named more quickly and accurately than pictures with low neighborhood frequency. These results show that the number of neighbors and the frequency of those neighbors influence lexical retrieval in speech production. The facilitative nature of these factors is more parsimoniously accounted for by an interactive model rather than by a strictly feedforward model of speech production.